SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The development of a novel decision support system for regional land use planning for brownfield land - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2024)

From data to decisions: Empowering brownfield redevelopment with a novel decision support system - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2023)

Exploratory analysis of machine learning techniques in the Nevada geothermal play fairway analysis - Connor M. Smith; James E. Faulds; Stephen Brown; Mark Coolbaugh; Jacob DeAngelo; Jonathan M. Glen; Erick R. Burns; Drew L. Siler; Sven Treitel; Eli Mlawsky; Michael Fehler; Chen Gu; et al. (Geothermics, 2023)

The NASA space weather science and observation gap analysis - Angelos Vourlidas; Drew Turner; Doug Biesecker; Anthea Coster; Alec Engell; George Ho; Thomas Immel; Catherine Keys; Louis Lanzerotti; Gang Lu; Noé Lugaz; Janet Luhmann; et al. (Advances in Space Research, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Digital tools for brownfield redevelopment: Stakeholder perspectives and opportunities - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Drew Hardy; Darren J. Beriro (Journal of Environmental Management, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Effects of Seagrass Wasting Disease on Eelgrass Growth and Belowground Sugar in Natural Meadows - Olivia J. Graham; Lillian R. Aoki; Tiffany Stephens; Joshua Stokes; Sukanya Dayal; Brendan Rappazzo; Carla P. Gomes; C. Drew Harvell (Frontiers in Marine Science, 2021)
Seagrass meadows provide valuable ecosystem benefits but are at risk from disease. Eelgrass ( Zostera marina ) is a temperate species threatened by seagrass wasting disease (SWD), caused by the protist Labyrinthula zosterae . The pathogen is sensitive to warming ocean temperatures, prompting a need for greater understanding of the impacts on host health under climate change. Previous work demonstrates pathogen cultures grow faster under warmer laboratory conditions and documents positive correlations between warmer ocean temperatures and disease levels in nature. However, the consequences of disease outbreaks on eelgrass growth remain poorly understood. Here, we examined the effect of disease on eelgrass productivity in the field. We coupled in situ shoot marking with high-resolution imagery of eelgrass blades and used an artificial intelligence application to determine disease prevalence and severity from digital images. Comparisons of eelgrass growth and disease metrics showed that SWD impaired eelgrass growth and accumulation of non-structural carbon in the field. Blades with more severe disease had reduced growth rates, indicating that disease severity can limit plant growth. Disease severity and rhizome sugar content were also inversely related, suggesting that disease reduced belowground carbon accumulation. Finally, repeated measurements of diseased blades indicated that lesions can grow faster than healthy tissue in situ . This is the first study to demonstrate the negative impact of wasting disease on eelgrass health in a natural meadow. These results emphasize the importance of considering disease alongside other stressors to better predict the health and functioning of seagrass meadows in the Anthropocene.

Montane Meadows: A Soil Carbon Sink or Source? - Cody C. Reed; Amy G. Merrill; W. Mark Drew; Beth Christman; Rachel A. Hutchinson; Levi Keszey; Melissa Odell; Sherman Swanson; Paul S. J. Verburg; Jim Wilcox; Stephen C. Hart; Benjamin W. Sullivan (Ecosystems, 2021)

Resource quality determines the evolution of resistance and its genetic basis - Katherine E. Roberts; Sean Meaden; Stephen Sharpe; Suzanne Kay; Toby Doyle; Drew Wilson; Lewis J. Bartlett; Steve Paterson; Mike Boots (Molecular Ecology, 2020)
Parasites impose strong selection on their hosts, but the level of any evolved resistance may be constrained by the availability of resources. However, studies identifying the genomic basis of such resource‐mediated selection are rare, particularly in nonmodel organisms. Here, we investigated the role of nutrition in the evolution of resistance to a DNA virus (PiGV), and any associated trade‐offs in a lepidopteran pest species ( Plodia interpunctella ). Through selection experiments and whole‐genome resequencing, we identify genetic markers of resistance that vary between the nutritional environments during selection. We do not find consistent evolution of resistance in the presence of virus but rather see substantial variation among replicate populations. Resistance in a low‐nutrition environment is negatively correlated with growth rate, consistent with an established trade‐off between immunity and development, but this relationship is highly context dependent. Whole‐genome resequencing of the host shows that resistance mechanisms are likely to be highly polygenic and although the underlying genetic architecture may differ between high and low‐nutrition environments, similar mechanisms are commonly used. As a whole, our results emphasize the importance of the resource environment on influencing the evolution of resistance.

A prospective comparative study of children with gastroenteritis: emergency department compared with symptomatic care at home - Otto G. Vanderkooi; Jianling Xie; Bonita E. Lee; Xiao-Li Pang; Linda Chui; Daniel C. Payne; Judy MacDonald; Samina Ali; Shannon MacDonald; Steve Drews; Lara Osterreicher; Kelly Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Comparative population genomics confirms little population structure in two commercially targeted carcharhinid sharks - Claudia Junge; Stephen C. Donnellan; Charlie Huveneers; Corey J. A. Bradshaw; Alexis Simon; Michael Drew; Clinton Duffy; Grant Johnson; Geremy Cliff; Matias Braccini; Scott C. Cutmore; Paul Butcher; et al. (Marine Biology, 2019)

Immune competence assessment in marine medaka (Orzyias melastigma)—a holistic approach for immunotoxicology - Roy R. Ye; Drew R. Peterson; Frauke Seemann; Shin-Ichi Kitamura; J. S. Lee; Terrance C. K. Lau; Stephen K. W. Tsui; Doris W. T. Au (Environmental Science and Pollution Research, 2017)

How Tidal Processes Impact the Transfer of Sediment from Source to Sink: Mekong River Collaborative Studies - Andrea Ogston; Mead Allison; Robin McLachlan; Daniel Nowacki; J. Drew Stephens (Oceanography, 2017)

A Three-Dimensional Mapping of the Ocean Based on Environmental Data - Roger Sayre; Dawn Wright; Sean Breyer; Kevin Butler; Keith Van Graafeiland; Mark Costello; Peter Harris; Kathleen Goodin; John Guinotte; Zeenatul Basher; Maria Kavanaugh; Patrick Halpin; et al. (Oceanography, 2017)

Examining the historical and present energy metabolism of a Rust Belt City: Syracuse, NY 1840–2005 - Stephen Balogh; Charles A. S. Hall; Drew V. Gamils; Alexander M. Popov; Ryan T. Rose (Urban Ecosystems, 2016)

Characterisation of major histocompatibility complex class I genes at the fetal-maternal interface of marsupials - Ina Buentjen; Barbara Drews; Stephen R. Frankenberg; Thomas B. Hildebrandt; Marilyn B. Renfree; Brandon R. Menzies (Immunogenetics, 2015)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Host inhibits replication of European porcine reproductive and respiratory syndrome virus in macrophages by altering differential regulation of type-I interferon transcriptional response - Tahar Ait-Ali; Alison D. Wilson; Wilfrid Carré; David G. Westcott; Jean-Pierre Frossard; Marnie A. Mellencamp; Daphne Mouzaki; Oswald Matika; David Waddington; Trevor W. Drew; Stephen C. Bishop; Alan L. Archibald (Immunogenetics, 2011)

REE and Sr isotope characteristics of carbonate within the Cu–Co mineralized sedimentary sequence of the Nchanga Mine, Zambian Copperbelt - Stephen Roberts; Martin R. Palmer; Matthew J. Cooper; Peter Buchaus; Drew Sargent (Mineralium Deposita, 2009)

Human‐induced changes in US biogenic volatile organic compound emissions: evidence from long‐term forest inventory data - Drew W. Purves; John P. Caspersen; Paul R. Moorcroft; George C. Hurtt; Stephen W. Pacala (Global Change Biology, 2004)
Volatile organic compounds (VOCs) emitted by woody vegetation influence global climate forcing and the formation of tropospheric ozone. We use data from over 250 000 re‐surveyed forest plots in the eastern US to estimate emission rates for the two most important biogenic VOCs (isoprene and monoterpenes) in the 1980s and 1990s, and then compare these estimates to give a decadal change in emission rate. Over much of the region, particularly the southeast, we estimate that there were large changes in biogenic VOC emissions: half of the grid cells (1°× 1°) had decadal changes in emission rate outside the range −2.3% to +16.8% for isoprene, and outside the range 0.2–17.1% for monoterpenes. For an average grid cell the estimated decadal change in heatwave biogenic VOC emissions (usually an increase) was three times greater than the decadal change in heatwave anthropogenic VOC emissions (usually a decrease, caused by legislation). Leaf‐area increases in forests, caused by anthropogenic disturbance, were the most important process increasing biogenic VOC emissions. However, in the southeast, which had the largest estimated changes, there were substantial effects of ecological succession (which decreased monoterpene emissions and had location‐specific effects on isoprene emissions), harvesting (which decreased monoterpene emissions and increased isoprene emissions) and plantation management (which increased isoprene emissions, and decreased monoterpene emissions in some states but increased monoterpene emissions in others). In any given region, changes in a very few tree species caused most of the changes in emissions: the rapid changes in the southeast were caused almost entirely by increases in sweetgum ( Liquidambar styraciflua ) and a few pine species. Therefore, in these regions, a more detailed ecological understanding of just a few species could greatly improve our understanding of the relationship between natural ecological processes, forest management, and biogenic VOC emissions.

Effect of ethylene and culture environment on development of papaya nodal cultures - Pablito M. Magdalita; Ian D. Godwin; Roderick a. Drew; Stephen W. Adkins (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)